Cultural Tourism in the Tourism Industry in Patan Area, Nepal - Shrestha, Rohit Kumar (Khwopa Journal, 2023)
The objectives of the study are to determine the benefit of cultural tourism for local people around Patan Darbar Square and assess the association between external tourist arrival for cultural tourism and income earning of Patan Darbar Square. This study was also based on both primary and secondary data The study used a descriptive research design and a case study method. This study adopted a qualitative method for the first objective of the study and a quantitative method for the second objective. Interviews were used for primary data. Interviews were conducted with culturalists, employees of Lalitpur Metropolitan City, and social workers within Patan Darbar Square in Nepal. Judgmental sampling techniques were adopted to collect primary data. Secondary data was collected from Lalitpur Metropolitan City of Lalitpur district. The simple correlation was used for quantitative data analysis whereas thematic analysis was used for qualitative data. According to the interview of research participants, cultural tourism provides benefits for local people around Patan Darbar Square in varied ways. There is a low positive correlation between external tourist arrival for cultural tourism and the income earning of Patan Darbar Square in Nepal. Practical implication of this study is that the metropolitan city should preserve and mobilize several tangible and intangible cultural heritages to earn much more foreign exchange.